2018
DOI: 10.1186/s12877-018-0865-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for an increased likelihood of a stable trajectory in mild cognitive impairment in individuals with higher motivational abilities

Abstract: BackgroundMotivational abilities (MA), that describe skills in relation to goal-oriented behavior, have recently been found to be associated with neuropathological aging. Here we examine the impact of MA on the long-term course of mild cognitive impairment (MCI).MethodsWe followed-up N = 64 individuals diagnosed with MCI (Mage = 73 years, 44% female) for 3 years. MA were assessed by long-term informants of the participants using two scales: motivation and decision regulation [Volitional Components Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Especially participants with higher self-paced motivated extracurricular activities profit from better executive functions scores at later life [ 101 , 102 , 107 109 ]. Executive functioning is crucial for mastering everyday life: A recent study demonstrated in 452 MCI patients that executive function is crucial for progression of MCI to dementia [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially participants with higher self-paced motivated extracurricular activities profit from better executive functions scores at later life [ 101 , 102 , 107 109 ]. Executive functioning is crucial for mastering everyday life: A recent study demonstrated in 452 MCI patients that executive function is crucial for progression of MCI to dementia [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the waitlist control group demonstrated the highest compliance (100%) among the four groups and the group did not show significantly lower performance compared to the cognitive training group or the exercise training group in any outcome measures. Studies have shown motivational abilities of persons with MCI, which include the ability to decide to do a specific task and the ability to stay with the task, may have protective influence on their cognitive decline and are associated with the stability of MCI [28, 29]. Further studies including psychological outcomes such as motivational abilities might help better understand the potential contributing factors involved.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies that applied diversely operationalised MR constructs found cross-sectional and longitudinal evidence for a protective influence of MR against abnormal cognitive decline (i.e. mild cognitive impairment, Alzheimer’s disease) in later life (Forstmeier and Maercker 2008 , 2015 ; Forstmeier et al 2012 ; Thoma et al 2018 ). Regarding general motivational abilities (e.g.…”
Section: Introductionmentioning
confidence: 99%